2018
DOI: 10.1155/2018/3403975
|View full text |Cite|
|
Sign up to set email alerts
|

Oxidative Stability of the Meat of Broilers Fed Diets Supplemented with Various Levels of Blackcurrant Extract (Ribes nigrum L.) during Different Time Period

Abstract: In the 20 d experiment, the influence of different concentration and supplementation period of commercial blackcurrant extract (BC) in the broiler diets on the oxidative stability of breast and thigh meat, as well as selected performance indices, was investigated. A number of 120 fifteen-d-old Hubbard Flex male chicks (initial BW 363.5 ± 22.9 g) were randomly allocated to five groups: the control and four treatments (6 replicates, 4 birds per cage in each group). The BC extract was administrated to treatment g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…Parallel results support the idea that lipid oxidation could be prevented by fortifying flavonoid antioxidants in animal feed [ 85 ]. Furthermore, supplementation of the broiler diet with blackcurrant-extract-rich-polyphenolic compounds enhanced the oxidative stability of their meat after 90 days of frozen storage [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parallel results support the idea that lipid oxidation could be prevented by fortifying flavonoid antioxidants in animal feed [ 85 ]. Furthermore, supplementation of the broiler diet with blackcurrant-extract-rich-polyphenolic compounds enhanced the oxidative stability of their meat after 90 days of frozen storage [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, rosemary extract gallocatechin derivatives (1.4%) and luteolin (1.0%) were quantified. The complete detailed polyphenolic composition found in BC extract was previously described in our associated publication [26]; therefore, the current composition is only presented as the main fractions. Briefly, the main polyphenolic fraction of BC consisted of anthocyanins (74.9%), followed by flavonols (14%), flavan-3-ols (6.1%), and derivatives of phenolic acids (4.9%).…”
Section: Experimental Design and Dietsmentioning
confidence: 99%
“…Acetonitrile was purchased from Merck (Darmstadt, Germany). The extracts were preliminarily tested for 1,1-diphenyl-2-picrylhydrazyl free radical (DPPH) to assess the synthetic capacity to neutralize the reactive oxygen species that are the main mediator of peroxidation process [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Rosemary extract and (OE) is one of the most popular natural additives have been tested in different food recently (Liu et al, 2009;Haile, 2015;Pereira et al, 2017;Al-Hijazeen, 2018). These medical plants extracts were evaluated directly through meat surface as (Velasco & Williams, 2011;Kumar et al, 2015;Zhai et al, 2018), mixing in ground meat (Ahn et al, 2007;Al-Hijazeen, 2014;Al-Hijazeen et al, 2016a, b;Zahid et al, 2018;Manessis et al, 2020), indirectly in the animal feed (Botsoglou et al, 2003;Ri et al, 2017;Sierżant et al, 2018;Cázares-Gallegos et al, 2019), and it mostly showed positive effect enhancing meat quality and extended their shelf-life.…”
Section: Introductionmentioning
confidence: 99%